Elements of teaching, institutionalisation and characteristic of judo in "Judo Kodokan Review" (1950-1969) - Przemysław Pawelec; Jong-Hoon Yu; Lothar Sieber (Kultura Media Teologia)
Background. Studies of judo and elements of the institutionalisation and characteristic of judo are usually carried from the perspective of the history of sport or the history of physical culture.